Congruency of the Goals and Objectives of a Graduate Program in Physical Education: An Assessment of Stakeholders Thru Importance-Performance Analysis Framework - Bryan M. Nozaleda; Ma. Haidee A. Mabborang (Kharkiv State Academy of Physical Culture, 2023)
Purpose: This study assessed the congruency of a graduate physical education program's goals and objectives using the Importance-Performance Analysis (IPA) framework. The research aimed to identify strengths, weaknesses, and opportunities for improvement, ultimately enhancing curriculum and bridging the gap between academia and the physical education and sports industry. Materials and Methods: a cross-sectional survey was conducted, utilizing a structured questionnaire distributed to 135 participants classified as internal and external stakeholders selected via purposive convenience sampling. The questionnaire was administered via Google Forms. The questionnaire consisted of items related to stakeholders' demographic profile, awareness, acceptability, and perceived levels of importance and performance of the goals and objectives of the program. Data analysis involved descriptive statistics, IPA, and Independent Samples T-test to determine varying perceptions among stakeholders. Results: The findings indicated a substantial degree of awareness and acceptability of the program's goals and objectives among stakeholders. The study also revealed a strong alignment between the program objectives, graduate school objectives, and the university's vision and mission. However, certain discrepancies emerged concerning stakeholders' acceptability levels for specific objectives. With regard to the importance-performance analysis, the results highlighted the need for the organization to enhance its performance in producing graduates possessing advanced disciplinary content knowledge. Graduates should be equipped to examine and appreciate both traditional and contemporary theories, concepts, and models within their respective disciplines. Conclusion: The study concludes that stakeholders have high awareness and acceptability of the preambular provisions of the university and the MPE program, but external stakeholders have lower awareness and acceptability. The congruency between program objectives and graduate school objectives, as well as the alignment between the university vision and graduate school vision and mission, suggests a well-designed and implemented program. Meanwhile, the importance-performance analysis highlights areas to improve, such as advanced disciplinary content, effective communication, and critical thinking and research skills. Enhancing communication and engagement strategies, monitoring alignment with stakeholder needs, and reassessing the importance of certain goals can improve the program's alignment with broader institutional goals and contribute to the university's overall success.